Cost Analysis and Pottery Manufacturing Returns: A Case Study of Jar Factories in Mueang Ratchaburi, Ratchaburi Province - Boonyoo, Sucharat; Wattanakanjana, Chantana; Khumruang, Parichart; Boonsuwan, Songsak; Boonyoo, Thanyanan; Charoensubmechok, Promporn; Duangjampa, Pornthip (Journal of Industrial Business Administration, 2023)
The objectives of this study were to explore the cost analysis and pottery manufacturing returns, which was the case study of jar factories in Mueang Ratchaburi, Ratchaburi province. This study was a qualitative study, which was an in-depth interview with 5 samples of pottery entrepreneurs of jar factories in Mueang Ratchaburi, Ratchaburi province. The research instrument in this study was an interview formed to serve the objectives of this study, whereas the data were analyzed using content analysis. Meanwhile, the interview data were analyzed in accordance with the cost and returns of production, production, and pottery returns. Findings in this study revealed that 1) cost and expenditures in pottery manufacture of 5 jar factories in Mueang Ratchaburi, Ratchaburi province included direct raw materials between 17,000 and 22,500 baht; direct wages between 366,300 and 480,000 baht; and variable manufacturing cost of between 177,360 and 229,152 baht and fixed manufacturing cost between 39,320 and 45,020 baht. 2) Pottery manufacturing returns included return on investment of from 22.75 to 1,487.45 baht; return on asset returns of total properties of between 24.18 and 1,252.77 baht; sales ratio per net sales of from 23.61 to 94.05 baht; profit ratio of operation per net sales of from 5.95 to 76.39 baht; and sales volume at break-even point was at 5 per each piece. The findings made it clearer about the production process that creates the production costs and returns of pottery. The information obtained can be used in planning and specifying production processes that can reduce costs and increase production yields.